2021
DOI: 10.1111/idh.12536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of toothbrush bristle stiffness and toothbrushing force on the abrasive dentine wear

Abstract: Besides dental plaque and external staining, toothbrushing can also remove some sound exposed dentin, the so-called 'abrasive dentine wear'. Abrasive dentine wear is a multifactorial process and could be affected by factors such as the abrasivity of the toothpaste, the applied brushing force and frequency of toothbrushing and the mechanical properties of the toothbrush, to name a few. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…These two observations contribute to the current uncertainty regarding the influence of bristle stiffness on the abrasive dentin wear. In a recent study by Hamza et al 12 , where the same soft- and medium parallel tuft toothbrushes were used as in this study (M43), same amounts of abrasive dentin wear were also observed between the two kinds of bristle stiffness at 2- and 3-N brushing force. On the other hand, another study by Bizhang et al 27 reported that soft bristle toothbrush caused statistically significantly higher abrasive dentin wear than medium bristle toothbrush, which is actually in agreement with the present findings with the crossed tuft design.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…These two observations contribute to the current uncertainty regarding the influence of bristle stiffness on the abrasive dentin wear. In a recent study by Hamza et al 12 , where the same soft- and medium parallel tuft toothbrushes were used as in this study (M43), same amounts of abrasive dentin wear were also observed between the two kinds of bristle stiffness at 2- and 3-N brushing force. On the other hand, another study by Bizhang et al 27 reported that soft bristle toothbrush caused statistically significantly higher abrasive dentin wear than medium bristle toothbrush, which is actually in agreement with the present findings with the crossed tuft design.…”
Section: Discussionsupporting
confidence: 64%
“…It is worth mentioning that the soft bristles in the previous study of Hamza et al 12 caused statistically significantly less abrasive dentin wear than the medium bristles when the brushing force reached 4 N. This was attributed to the fact that the soft bristles deflected much more than the medium bristles at such brushing force and dragged less abrasive particles on the samples’ surface. Considering this finding, it could theoretically be assumed that crossed tuft design would rather prevent the bristles from getting deflected in comparison to the parallel tuft design, and therefore cause more abrasive wear.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…An alternative strategy to reduce the force transmitted to the teeth during brushing is to use softer bristles, and previous studies have investigated the relationship between bristle stiffness and abrasive dentine wear, a correlate of transmitted force [ 23 , 26 30 ]. However, whilst some studies suggest that softer bristles are associated reduced dentine abrasion [ 23 , 27 , 28 ], others indicate the opposite [ 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article reports data from two studies that assessed experimental toothbrush designs (GSK Consumer Health), which incorporates a flexible element in their necks, designed to look like a ball joint, between the toothbrush head and handle. Manual toothbrush users typically employ brushing forces of approximately 1.5–3.25 N, [ 17 21 ] and previous studies have shown that higher brushing force directly correlates with higher abrasive dentine wear [ 22 , 23 ]. These experimental product designs aim to change the angle of the brushing head towards the inbetween regions of buccal and lingual/palatinal tooth surfaces, and to reduce the brushing force that is transmitted to the tooth and gum surfaces.…”
Section: Introductionmentioning
confidence: 99%